Description of a new species of the Anthaxia (Anthaxia) glabrifrons species-group from Morocco (Coleoptera: Buprestidae: Anthaxiini) - Obořil, Martin; Baňař, Petr (Zootaxa, 2022)
Anthaxia (Anthaxia) rejzeki sp. nov. belonging to the Anthaxia (Anthaxia) glabrifrons species-group from Morocco is described, illustrated and compared to other species of the group.